The Relationship between Mental Toughness and Competitive Anxiety of Diving Athletes in the Training Phase - Wildhan Rahmadian Sofyan; Dede Rohmat Nurjaya; Mulyana (Journal of Physical Education Health and Sport, 2024)
There are main factors that can reduce the level of competitive anxiety in athletes, namely mental toughness, this is proven in research on other sports but has not been done in the sport of diving. This study aims to examine the significant relationship between mental toughness and competitive anxiety of diving athletes in the training phase. The method used is descriptive correlation using the Sport Mental Toughness Questionnaire (SMTQ) instrument and the Sport Competitive Anxiety Test (SCAT) questionnaire. The research sample amounted to 24 diving athletes at the West Java level, Data collection through google form in the form of questionnaires and data analysis techniques with SPSS version 26. The results of data analysis show that there is a significant negative relationship with a pearson correlation value of -0.415 with a Sig value. (2-tailed) 0.044 Based on the test results, the value of Sig. (2-tailed) <0.05 so that H0 is rejected. This study concludes that there is a significant relationship between mental toughness and competitive anxiety in the training phase